From vision to action : how to put some oomph into the Millennium Development Goals - Boughton, James (2004)
Looks at the assessment of progress toward the MDGs outlined in the World Bank and IMF report entitled 'The global monitoring report'. Highlights the priorities for developing and developed countries and those for international financial institutions.